Open science and public trust in science: Results from two studies. (November 2022) - Rosman, Tom; Bosnjak, Michael; Silber, Henning; Koßmann, Joanna; Heycke, Tobias
In two studies, we examined whether open science practices, such as making materials, data, and code of a study openly accessible, positively affect public trust in science. Furthermore, we investigated whether the potential trust-damaging effects of research being funded privately (e.g. by a commercial enterprise) may be buffered by such practices. After preregistering six hypotheses, we conducted a survey study (Study 1; N  = 504) and an experimental study (Study 2; N  = 588) in two German general population samples. In both studies, we found evidence for the positive effects of open science practices on trust, though it should be noted that in Study 2, results were more inconsistent. We did not however find evidence for the aforementioned buffering effect. We conclude that while open science practices may contribute to increasing trust in science, the importance of making use of open science practices visible should not be underestimated.